Evaluation of Hypertension Control Program Through Chayote Juice in Sunggumanai Hamlet, Parangloe - Mardatillah, Nur Ilmi; Amalia, Alfiyyah; Miftahussahada, Miftahussahada; Hikmah, Nurul (Unihealth Community Research, 2026)
Hypertension is a major non-communicable disease that requires continuous promotional and preventive efforts. One community-based intervention involved hypertension education accompanied by a demonstration of chayote (Sechium edule) juice preparation as a non-pharmacological approach. This study aimed to evaluate the sustainability of the program and identify factors influencing its implementation six months after the intervention. The evaluation was conducted as part of a Community-Based Learning Program using the Asset-Based Community Development (ABCD) approach. It involved 23 participants in Sunggumanai Hamlet, Belapunranga Village, Gowa Regency. Data were collected through structured interviews and analyzed descriptively. The results showed that 69.6% of respondents no longer consumed chayote juice, although 82.6% reported that it was easy to prepare independently. These findings indicate that ease of implementation alone is insufficient to ensure sustained adoption. Therefore, appropriate participant selection, continuous follow-up, and stronger family involvement are needed to improve the sustainability of community-based health promotion programs.